REMOTE MONITORING OF PATIENTS WITH LONG-TERM MECHATRONIC CIRCULATORY SUPPORT SYSTEM - A. V. Adaskin; K. N. Dozorov; I. A. Filatov; G. P. Itkin (Вестник трансплантологии и искусственных органов)
The article describes the technology of remote patient monitoring and the parameters of circulatory assist device AVK-N as well as the advantages of said technology to improve the efficiency of personalized medicine in diagnosis and treatment of patients with AVK-N in the postoperative period. Authors show the capabilities of remote monitoring technology to determine the location of the patient by satellite navigation in the case of emergency call for medical and technical services, and present the structure and modes of the displayed information for mobile devices and Web-server. Doctor-patient interaction based on remote monitoring technology via mobile/ satellite/wired Internet is also shown.